Comparative therapeutic evaluation of 308 nm monochromatic excimer light in combination with calcipotriol ointment vs 308 nm monochromatic excimer light alone in palmoplantar psoriasis - Poulkar, Chandrakant B.; Chaudhari, Nitin D.; Khatu, Swapna S.; Patwekar, Shilpa L. (International Journal of Research in Dermatology, 2019)
Background: Palmoplantar psoriasis is difficult to treat and often recalcitrant to traditional treatment modalities like topical steroids, anthralin, calcipotriol, methotrexate, cyclosporine, NB-UVB and PUVA. This study was aimed to compare efficacy of 308 nm monochromatic excimer light (MEL) in combination with calcipotriol ointment to 308 nm MEL alone in treatment of palmoplantar psoriasis. Methods: This self-control study was conducted in 30 patients of palmoplantar psoriasis. Right side was treated with 308 nm MEL, 2 times/week, at meantime calcipotriol ointment was applied externally, 2 times/day (treatment group); the left side was treated with 308 nm MEL alone, 2 times/week (control group). Erythema, scaling, induration and fissuring (ESIF) score and cumulative doses of 308 nm MEL were assessed before treatment and on weeks 2, 4 and 6 after initiation of treatment. Results: All 30 patients completed the treatment. ESIF scores on week 2, week 4, and week 6 in treatment group were significantly lower than control group (p<0.01). The average cumulative MEL dose in treatment group at the end of trial was 8.12±1.72 J/cm2, which was significantly lower than in control group 12.76±1.92 J/cm2 (p<0.01). Conclusions: Treatment of palmoplantar psoriasis with 308 nm MEL in combination with external application of calcipotriol ointment can improve long-term treatment efficacy, decrease cumulative doses, and adverse effects induced by MEL irradiations.